The influence of some fungicides on the population of Rhizoctonia solani kuhn in soil and the incidence of fruit root of processing tomato - Souza Filho, Benedito Fernandes de (Pesquisa Agropecuaria Brasileira, 2014)
The effect of four fungicides on the population of R. solani in soil and the incidence of fruit rot of processing tomato was evaluated under field conditions. The saprophytic activity of R. solani, estimated as frequency of isolation, was significantly reduced by three applications of either pentachloronitrobenzene of chlorothalonil at 8 days intervals. Three applications of chlorothalonil significantly reduced also the incidence of tomato fruit caused by R. solani. A positive correlation was found between tomato fruit and isolation of R. solani from soil eight days after the third fungicidal application.
Keywords: Lycopersicon esculentum; saprophytic activity; inoculum/disease correlation; chemical control; soil fungi isolation